The new politics of Russia: Interpreting change - Monaghan, Andrew (2016)
From the conflict in Syria to the crisis in Ukraine, Russia continues to dominate the headlines. Yet the political realities of contemporary Russia are poorly understood by Western observers and policy-makers. Andrew Monaghan explains the importance of 'getting Russia right'. Exploring in detail the relationship between the West and Russia, he charts the development of relations and investigates the causes of the increasingly obvious sense of strategic dissonance. He also considers the evolution in Russian domestic politics, introducing influential current figures and those who are forming the leadership and opposition of the future. By delving into the depths of difficult questions such as the causes of the Ukraine crisis or the political protests surrounding the 2011–12 elections, the book offers a dynamic model for understanding this most fascinating and elusive of countries.